Performance, carcass precentages and heterosis values, Alabio and Cihateup line and crossbreeding on eight week old - P.R. Matitaputty; R.R. Noor; P.S. Hardjosworo; C.H. Wijaya (Indonesian Center for Animal Research and Development (ICARD), 2011)
One effort for improving the productivity of Indonesian local ducks in particular as a meat types is by crossing among the local ducks. Crossbreeding is a fast breeding program for improving some commercial traits. Crossing between two lines or different breed are often used in production systems to utilized the advantage of heterosis (hybrid vigor). Crossbreeding is expected to produce new synthetic strains of duck that perform better than their parents. This study aims to utilize the heterosis and determine best cross, and to study the performance changes due to crossbreeding. The statistical design used in this study was a randomized complete design (RCD) consisting of 4 treatments with 6 replications, each replication consisting of five ducks. The treatments used were the crossing of the pure Cihateup ♂ x Cihateup ♀ (CC), line Alabio ♂ x Alabio ♀ (AA), Alabio ♂ x Cihateup ♀ (AC) cross as well as Cihateup ♂ x Alabio ♀ (CA) cross. This study using male ducklings first hybrid (F1). The results show that the CA is better than AC in the final live weight (7.05%), weight gain (7.32%), carcass weight (9.24%) and carcass yield (2.55%). Fleshy carcass cuts such as breast meat of AA (6.13%) is better when compared to the others, but the highest percentage of meat percentage of the thigh is the AC (10.13%). Duck crossesing CA possess superior properties more and economic value compared with the duck AC. Key Words: Alabio Duck, Cihateup Duck, Crossing, Heterosis, Performance